“Kapsukism” and the “Angarietists”: The Conflict between Leaders of the Communist Party of Lithuania in 1926–1927 - Ėmužis, Marius (Lietuvos istorijos studijos, 2021)
From about 1923 onwards, two leaders of the Communist Party of Lithuania (CPL), Zigmas Aleksa-Angarietis and Vincas Mickevičius-Kapsukas, began to disagree on the tactics and direction of the party. In 1925–1926, because of the workload in the Comintern apparatus and the subsequent illness of V. Kapsukas, Z. Angarietis began to dominate in CPL matters and isolated V. Kapsukas from decision-making within the CPL and information pertaining to it. When V. Kapsukas recovered from his illness, he sought to recover his positions and wrote an appeal to the Comintern Executive Committee, asking the committee to resolve the conflict. Because of this, the conflict got more personal: both individuals started to gather supporters, initiating a power struggle for leadership positions, while the conflict itself, beginning with a disagreement about tactics, evolved into a personal matter. The Comintern formed a commission to resolve the conflict, but they took a balancing position: the commission wanted to maintain the status quo, but instead managed only to delay and not resolve the conflict.